Genesis of the Daping Gold Deposit in the Middle Xuefeng Mountain Area, Southern China: Constraints from Geochemistry, Fluid Inclusion, and H-O-S Isotope - Xu Kong; Wen-Tian Mi; Xue-Yuan Qi; Shu-Jun Lǚ; Yu-Jun Dong; Jie Xin (Geofluids)
The medium-sized Daping gold deposit is located in the middle Xuefeng Mountain area of Southern China with gold ores hosted in sericite phyllite, sericitolite, and mylonite. The auriferous quartz-carbonate-sulfide veins and adjacent alteration rocks are structurally controlled within the NE (northeast) shear zone with NE, NNE (north-east-east), and NW (northwest) trending at high inclination angles. The petrogeochemistry analysis results show that the gold ores are characterized by high content values of SiO2, S, and As and low content values of Al2O3 and Na2O and display strong enrichment of LREE with δEu values ranging from 0.54 to 0.75. Four stages of mineralization/alteration were identified: the first stage has mineral assemblages of quartz+pyrite+arsenopyrite±carbonate minerals, the second stage has mineral assemblages of quartz+polymetallic sulfide minerals (pyrite, arsenopyrite, chalcocite, galena, chalcopyrite, tetrahedrite)±chlorite±carbonate minerals, the third stage has mineral assemblages of quartz and carbonate minerals, and the supergene stage is characterized by limonite±patina which were formed by the oxidation of metal sulfides. Among them, the first stage and the second stage are the main gold mineralization stages. The ore-forming fluid inclusions in quartz are mainly composed of liquid phase (H2O) and gas phase (H2O and CO2), and based on the microthermometric analysis, the first metallogenic stage and second metallogenic stage yielded average homogenization temperature of 184.5 and 255.8°C and average salinity of 7.64 wt.% NaCl eqv. and 11.35 wt.% NaCl eqv., respectively. Thus, the ore-forming fluids belong to H2O-CO2-NaCl, medium-low temperature, and medium-low salinity fluid. The δDH2O and δ18OH2O values of auriferous quartz are from -51‰ to 62‰ and from -1.44‰ to 5.42‰, respectively, indicating that the ore-forming fluids may belong to mixing fluids of the magmatic fluid and meteoric hydrothermal fluid. The values of δ34S of metal sulfides range from -0.94‰ to 1.98‰ (-0.131‰ in average), implying that sulfur may source from the concealed granite and/or basement metamorphic strata. The Daping gold deposit formed in the Indosinian period under the tectonic environment of compression between the Cathaysian plate and Yangtze plate and may belong to orogenic gold deposits.